The Effect of Snail Mucus (Achatina Fulica) Toward The Activity and Chronicity Indices of Renal Histology in Pristane-Induced Lupus Nephritis Mice Model - Nurudhin, Arief; Prabowo, Nurhasan Agung; Werdiningsih, Yulyani; Budiningsih, Fatichati; Maharani, Tiara; Karyawinara, Agung; Widyastuti, Retno (Bangladesh Journal of Medical Science, 2023)
Background: Snail mucus (Achatina Fulica) has been known to contain heparan sulfate, and acharan sulfate, a glycosaminoglycan with anti-inflammatory properties and might repair the injured glomeruli. Aim: This study aims to find the effect of snail mucus on activity and chronicity indices of renal histology in a pristane-induced lupus nephritis mice model. Method: This was an experimental study with a post-test-only control group design using 42 mice strains Balb/C. Mice were randomized into six groups: control, lupus nephritis, methylprednisolone, snail mucus 0.5 ccs, snail mucus 0,5 cc and methylprednisolone, and snail mucus one cc and methylprednisolone group. Result: Snail mucus significantly affected the activity index (p = 0.001). The lowest activity index was shown by snail mucus one cc and methylprednisolone group. While the chronicity index was not significantly affected by the snail mucus with p = 0.195. Snail mucus decreases the activity index of renal histology in the pristane-induced lupus nephritis mice model but not the chronicity index. Bangladesh Journal of Medical Science Vol. 22 No. 03 July’23 Page : 515-520